(3TQM fXe GdLGeY GdcHjQs - (3CHh GdbGSe eMehO Hf YHjO Gddg Hf UGYO GdMGQKis; (3CMeO Hf CHj GdeDjO GdeMehOj GdfSajs
(3ChdgG (B:s
(3ai GdUdGI HGdUdhJjI hde jSLO MJi TQY ai GdUdGI s
(3BNQgG (B:s
(3ZjQ hGVMg ai GdJUhjQ s
(3GdLGeY GdcHjQ ddTjHGfi GfXQ cTa GdXfhf L(B1 (3U` (B567s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B- (3GdLRA (B1 - (3U (B567 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B570s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfajs